Karakteristik Morfometri Testis dan Tingkat Motilitas Sperma Kucing Berdasarkan Variasi Umur di Kota Pekanbaru, Indonesia: Testicular Morphometric Characteristics and Sperm Motility Levels of Cats Based on Age Variations in Pekanbaru City, Indonesia - Putri, Frilianty; Suprayoga, Tito; Pratama, Hadimas Bakti; Fani, Rifia Tiara; Fitranda, Mulya; Alkausar, Triawan; Suhandri, Wiwin; Jaya, Indra; Radja, Anggrek Citadika Ratu; Zakiah, Debita (BPFP Universitas Bengkulu, 2025)
This study aimed to analyze the effect of age variation on testicular morphometry and spermatozoa motility in cats. A total of 21 male cats were grouped into three age categories (< 1 year, 1–3 years, and 3 years). The testes were collected through an open castration procedure, and their morphometric parameters (length, width, and circumference) were measured. Semen samples were obtained by incising the cauda epididymis of each testis to evaluate its motility level under a light microscope. Data were analyzed using one-way Analysis of Variance (ANOVA), followed by the Tukey test to identify differences between groups. The results showed that age variation did not cause a significant difference in the morphometric characteristics of the collected testes (P>0.05). However, a significant difference was found in spermatozoa motility levels among the different age groups. It is concluded that age does not affect the physical dimensions of the testis but has a significant influence on the functional quality of spermatozoa. The 1–3 year-old group showed the optimal level of spermatozoa motility compared to the other age groups in this study